Usulan Penyeimbangan Lintasan Produksi pada Line Final Assembling KWh OB91Z Guna Meningkatkan Efisiensi Lintasan Produk - Siti Aisyah; Mediana Mediana (Universitas Bunda Mulia, 2017)
Smooth production in a manufacturing firm is very important because it will affect the outcome of which is the expected output of the production trajectory balance that existed at the company if it is optimal or not. The objectives to be achieved in this research is balancing production trajectory so that the expected target company can be reached, drink idle time, and improve the efficiency of the production trajectory. At PT METBELOSA there are trajectories that have not been balanced by the production of idle time on the final line for assembling OB91Z 1.606149 minutes, balance delay in assembling the final line OB91Z by 29.75% and the efficiency in assembling the final line OB91Z of 70.25%, from Data collection on the final assembling line OB91Z also note that the company can’t achieve the expected production targets every day as many as 1500 kwh meter OB91Z type. Therefore the company needs to make improvements in the balancing path to reach their intended target in the final assembling line OB91Z. The method used is a heuristic method MALB (Mansoor Aided Line Balancing) and heuristic methods COMSOAL (Computer Method for Sequencing Operations for Assembly Lines). The data used is data on the production process of assembling the final line OB91Z and the amount of labor in assembling the final line OB91Z. After making improvements by using heuristic methods MALB (Mansoor Aided Line Balancing) then the balance delay becomes 14.62% and 85.38% effeciency be.Keywords: Line Balancing, MALB, COMSOAL, Efficiency, Balance Delay, Work Station